Well-being Practices, Rhythms, and Commitments: Perspectives from Early-Career Teachers in British Columbia, Canada - Harback, Andrew; Huizenga, Hyne-Ju; Kutsyuruba, Benjamin (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
One of the ways to address stress and burnout in the teaching profession is by paying attention to teacher well-being. Seligman (2011) argued that there are five pillars of emotional health: positive emotions, engagement, positive relationships, meaning, and accomplishment, also known as the PERMA theory of well-being. This article details an action-research study that examined what PERMA-related practices, rhythms, and commitments teachers in British Columbia believed were the most influential in contributing to their overall wellness. Eight initial participants, who taught full-time, had at least three years of experience, and generally enjoyed their profession, were recruited from a public school and an independent school in British Columbia, Canada. Initial participants completed a quantitative well-being assessment known as the PERMA-Profiler, to identify a group of three teachers who would be appropriate for participation in the follow-up, qualitative, one-on-one interviews. Content analysis of teacher perspectives revealed an emphasis on the actions related to three key themes: the power of relationships, practicing gratitude through reflection, and intentionality surrounding time investment and allocation. This article concludes with implications for how to help teachers flourish, describing various practices, rhythms, and commitments that are beneficial for educators’ pursuits of emotional wellness.